2018
DOI: 10.1186/s11671-018-2792-y
|View full text |Cite
|
Sign up to set email alerts
|

Interplay Effect of Temperature and Excitation Intensity on the Photoluminescence Characteristics of InGaAs/GaAs Surface Quantum Dots

Abstract: We investigate the optical properties of InGaAs surface quantum dots (SQDs) in a composite nanostructure with a layer of similarly grown buried quantum dots (BQDs) separated by a thick GaAs spacer, but with varied areal densities of SQDs controlled by using different growth temperatures. Such SQDs behave differently from the BQDs, depending on the surface morphology. Dedicated photoluminescence (PL) measurements for the SQDs grown at 505 °C reveal that the SQD emission follows different relaxation channels whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 26 publications
0
9
0
1
Order By: Relevance
“…Additional STEM and EDX images are given in the Supporting Information (Figures S1 and S2). First, almost pure InP surface quantum dots (QDs) are evidenced in Figure c (black circular areas) and in Figure j, arising from demixion due to the non-equilibrium growth conditions used . Removal of these surface QDs will be discussed hereafter.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional STEM and EDX images are given in the Supporting Information (Figures S1 and S2). First, almost pure InP surface quantum dots (QDs) are evidenced in Figure c (black circular areas) and in Figure j, arising from demixion due to the non-equilibrium growth conditions used . Removal of these surface QDs will be discussed hereafter.…”
Section: Results and Discussionmentioning
confidence: 99%
“…First, almost pure InP surface quantum dots (QDs) are evidenced in Figure 1c (black circular areas) and in Figure 1j, arising from demixion due to the non-equilibrium growth conditions used. 20 Removal of these surface QDs will be discussed hereafter. Second, a preferential incorporation of In in the close vicinity of the antiphase boundary singularity is observed, together with an In-rich phase at the surface where the singularity emerges.…”
Section: Resultsmentioning
confidence: 99%
“…4, c и d, точки). Из полученных зависимостей виден значительный длинноволновый сдвиг пиков ФЛ с увеличением температуры, что ранее уже отмечалось в литературе как для КТ InAs/GaAs [33,34], так и для КТ In 0.8 Ga 0.2 As [35]. С использованием формулы Варшни [36,37]…”
Section: оптические свойства квантовых точек Inas и Ingaasunclassified
“…Due to the special surface sensitivity, it is expected that these SQDs should be good materials to function as humidity sensors [10,11]. Thus, a recent surge in research into the surface-sensitive performance of InGaAs SQDs has been reported [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%